2018
DOI: 10.3389/fnmol.2018.00439
|View full text |Cite
|
Sign up to set email alerts
|

New Features on the Expression and Trafficking of mGluR1 Splice Variants Exposed by Two Novel Mutant Mouse Lines

Abstract: Metabotropic glutamate receptors (mGluRs) couple to G-proteins to modulate slow synaptic transmission via intracellular second messengers. The first cloned mGluR, mGluR1, regulates motor coordination, synaptic plasticity and synapse elimination. mGluR1 undergoes alternative splicing giving rise to four translated variants that differ in their intracellular C-terminal domains. Our current knowledge about mGluR1 relates almost entirely to the long mGluR1α isoform, whereas little is known about the other shorter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…mGlu receptor signaling is regulated at several levels that could vary by sex. One possibility is that Grm1 could display sex differences in splicing [73], leading to differences in subcellular protein expression and effector signaling [74,75]. Indeed, studies in hippocampal interneurons found that mGlu 1 and mGlu 5 receptors can activate distinct signaling pathways to regulate calcium mobilization [72], illustrating that mGlu 1 and mGlu 5 receptors could depolarize PV-INs through divergent mechanisms and these could also vary by sex.…”
Section: Discussionmentioning
confidence: 99%
“…mGlu receptor signaling is regulated at several levels that could vary by sex. One possibility is that Grm1 could display sex differences in splicing [73], leading to differences in subcellular protein expression and effector signaling [74,75]. Indeed, studies in hippocampal interneurons found that mGlu 1 and mGlu 5 receptors can activate distinct signaling pathways to regulate calcium mobilization [72], illustrating that mGlu 1 and mGlu 5 receptors could depolarize PV-INs through divergent mechanisms and these could also vary by sex.…”
Section: Discussionmentioning
confidence: 99%
“…We previously generated mGluR1a-P/E-rescue mice expressing mGluR1a with a point mutation (proline (P) 1153 to glutamate (E)) in its Homer binding domain. We found that the P/E-mutant mGluR1a deficient for Homer binding did not significantly alter its distribution at perisynaptic sites of parallel fiber-PC synapses and rescued impaired motor coordination observed in mGluR1-KO mice [31]. Taken together with the lower amount of Homer binding with mGluR5 homodimers in mGluR5-rescue mice, the binding of Homer to mGluR1/5 may not contribute significantly to group I mGluR function in PCs.…”
Section: Discussionmentioning
confidence: 73%
“…mGlu 1 β is a short alternatively spliced variant of the Grm1 gene in which the last 318 amino acid residues of the mGlu 1 α variant are replaced by 20 different residues [1]. Available evidence suggests that mGlu 1 α and mGlu 1 β variants heterodimerize both in vitro and in vivo [48][49][50] which affects receptor trafficking to the plasma membrane of Purkinje cell [46,47]. In line with these previous findings, we were able to identify specific mGlu 1 β peptides in five out of six experiments, despite the fact that the specific portion of the mGlu 1 β variant is quite short.…”
Section: Immunoprecipitation Of Mglu1α From Mouse Cerebellummentioning
confidence: 99%